New insights from multi-proxy data from the West Antarctic continental rise: Implications for dating and interpreting Late Quaternary palaeoenvironmental records. (1st April 2021) - Hillenbrand, C.-D.; Crowhurst, S.J.; Williams, M.; Hodell, D.A.; McCave, I.N.; Ehrmann, W.; Xuan, C.; Piotrowski, A.M.; Hernández-Molina, F.J.; Graham, A.G.C.; Grobe, H.; Williams, T.J.; et al.
Abstract: The Antarctic Peninsula's Pacific margin is one of the best studied sectors of the Antarctic continental margin. Since the 1990s, several research cruises have targeted the continental rise with geophysical surveys, conventional coring and deep-sea drilling. The previous studies highlighted the potential of large sediment drifts on the rise as high-resolution palaeoenvironmental archives. However, these studies also suffered from chronological difficulties arising from the lack of calcareous microfossils, with initial results from geomagnetic relative palaeointensity (RPI) dating promising a possible solution. This paper presents data from new sediment cores recovered on cruise JR298 from seven continental rise sites west of the Antarctic Peninsula and in the Bellingshausen Sea with the objectives to (i) seek calcareous foraminifera, especially at shallow drift sites, to constrain RPI-based age models, and (ii) investigate the depositional history at these locations. We present the results of chronological and multi-proxy analyses on these cores and two cores previously collected from the study area. We establish new age models for the JR298 records and compare them with published RPI-based age models. In addition, we evaluate the reliability of different palaeoproductivity proxies and infer depositional processes. Planktic foraminifera are present in various core intervals. Although their stable oxygen isotope (δ 18 O) ratios, tephrochronological constraints and glacial-interglacial changes in sediment composition provide age models largely consistent with the RPI chronologies, we also observe distinct differences, predominantly in the Bellingshausen Sea cores. Enrichments of solid-phase manganese together with evidence for "burn-down" of organic carbon in late glacial and peak interglacial sediments document non-steady-state diagenesis that may have altered magnetic mineralogy and, thus, RPI proxies. This process may explain discrepancies between RPI-based age models and those derived from δ 18 O data combined with tephrochronology. The data also indicate that organic carbon is a much less reliable productivity proxy than biogenic barium or organically-associated bromine in the investigated sediments. In agreement with previous studies, sediment facies indicate a strong control of deposition on the rise by bottom currents that interacted with detritus supplied by meltwater plumes, gravitational down-slope transport processes and pelagic settling of iceberg-rafted debris (IRD) and planktic microfossils. Bottom-current velocities underwent only minor changes over glacial-interglacial cycles at the drift crests, with down-slope deposition only rarely affecting these shallow locations. Maximum concentrations of coarse IRD at the seafloor surfaces of the shallow sites result predominantly from upward pumping caused by extensive bioturbation. This process has to be taken into account when past changes in IRD deposition are inferred from quantifying clasts >1 mm in size. Highlights: Shallow drift sediments from the Antarctic rise bear calcareous foraminifera. Relict redox fronts and organic carbon burn-down prove non-steady-state diagenesis. Bioturbation causes some stratigraphic displacement of gravelly ice-rafted debris. Biogenic bromine is a reliable paleoproductivity proxy in Southern Ocean sediments.